Dynamic shifts in trophoblast nucleos(t)ide metabolism, transport, and adenosine signaling during gestation and preterm birth - Mohammed Ali; Mariia Adler; Antonin Libra; Ivan Vokral; Rona Karahoda; Eva Cifkova; Miroslav Lisa; Jakub Tomek; Magdalena Novotna; Frantisek Staud; Lukas Cerveny (Scientific Reports)
Abstract Nucleos(t)ides are essential for DNA/RNA synthesis, energy metabolism, and signaling, yet their roles in placental development remain poorly understood. The placenta undergoes dynamic metabolic adaptations throughout gestation to support fetal growth. This study investigates gene expression shifts in nucleos(t)ide metabolism, transport, and adenosine signaling during placental development and in the pathological condition of spontaneous preterm birth (PTB). We analyzed gene expression in first-trimester (n = 10) and term (n = 10), and PTB (n = 10) human placentas, and in cytotrophoblast and syncytiotrophoblast stage in primary human trophoblasts (n = 3) and BeWo (n = 5) cells. For developmental context, rat placentas were examined at gestation days (GD) GD12, GD15, and GD20 (n = 5 per group) that correspond to early second trimester in the human placenta. We found that genes involved in nucleos(t)ide metabolism and adenosine signaling were dominantly upregulated from early gestation to term in the human placenta. PTB placentas revealed further elevation compared to the term placenta. Differentiation from cytotrophoblast to syncytiotrophoblast was accompanied by only minor changes. Pearson’s correlation analysis revealed strong gene-metabolite and gene-gene associations, highlighting an integrated metabolic network regulating placental function. Gene expression also differed among the tested GDs in the rat placenta. These findings demonstrate dynamic changes of nucleos(t)ide metabolism during healthy placental development and enhanced expression in PTB placentas, suggesting increasing needs for nucleos(t)ides during placental growth and metabolic shifts in the PTB placenta. Our data also indicate that nucleos(t)ide metabolism is preserved in both proliferative and differentiated states.